Certification of Natural Wine: Policy Controversies and Future Prospects - Alonso González, Pablo; Parga Dans, Eva; Fuentes Fernández, Rosana (Frontiers in Sustainable Food Systems, 2022)
Natural wine is made from grapes produced under organic or biodynamic management without using additives in the cellar. Natural wine represents a movement of winegrowers that see agriculture as an ethical act against wine industrialization and as a way to make food systems more sustainable. The movement has gained fast-growing global fame and connects rural producers with urban consumers. The recent French recognition of a natural wine certification has spurred discontent among other European countries and wine business associations. A debate about the policy implications of natural wine certification is necessary in order to shed light on the matter. This paper calls for transparency in the labeling of wine ingredients, in line with recent consumer demands, which would make the creation of new certifications redundant.